PROPOSTA PARA A CONSTRUÇÃO UM SISTEMA INFORMATIZADO PARA GESTÃO INTEGRAL DE RISCOS DE DESASTRES NATURAIS (SIGRID) NO CENÁRIO BRASILEIRO - Gregorio, Leandro Torres Di; Soares, Carlos Alberto Pereira; Saito, Silvia Midori; Soriano, Erico; Londe, Luciana de Resende; Coutinho, Marcos Pellegrini (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2013)
This work presents a design for an Integrated Management System of Natural Disasters Risks (SIGRID), based on literature review about integral management of disasters risks and also on the authors’ experience related to operational and inter-institutional situations in the Brazilian protection and defense civil scenario. The combined analysis of the main current Brazilian systems was the starting point for the creation of this proposal. Those systems (System for Monitoring and Warnings of Natural Disasters/MCTI, System for Urban Occupation Monitoring/MCid and System for Information about Disasters/MI) provide complementary information and are responsible for joining information and other related systems in different scales (including municipalities, state and the whole country in some cases). The needs and the conceptual  inter-operational arrangement among systems were analyzed and the new system’s main characteristics and functions were defined. The proposed system’s mission highlights the connection of activities related to the Integral Management of Disasters Risks in Brazil, considering peculiarities of the country’s federative pact. The proposal is in accordance with the Brazilian Law 12.608/12.